Conscience and Context: the Popish Plot and the Politics of Ritual, 1678–1682 - Beaver, Daniel C. (The historical journal, 1991)
The Popish Plot is the proper starting point for a reassessment of society and culture in late seventeenth-century England. The origins of the plot have become increasingly obscure, primarily because historians have made the erosion of Calvinist religious values and belief a defining characteristic of social and political change after the Restoration. John Kenyon has argued that the plot was an instance of mass hysteria, with its roots in the overcrowded, rumour-infested environment of London. Having identified post-Restoration nonconformity with cranks mentally ‘unhinged’ by the civil wars and the Great Fire, Kenyon interprets the plot as an obvious fabrication foisted on a paranoid and credulous nation by adventurers and religious extremists. Christopher Hill, in rare agreement with Kenyon, sees the decline of the religious approach to politics until ‘by the time of the Popish Plot it had degenerated into a stunt manipulated by cynical politicians’.